Antisipasi dan Kesiapan Komunitas: Menelusuri Adaptasi Masyarakat Bidara Cina terhadap Ancaman Banjir - Bagas Hardianto; Rayuna Handawati; Ilham Badaruddin Mataburu (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the form of adaptation of the Bidara Cina Village community. The method used is qualitative with the technique of Validity of triangulation data. The informant in this study was a resident of Bidara Cina Village, supported by the Head of Section (KASI) of the Bidara Cina Village Government and the Head of RW. The results showed that the community has new adaptations used in dealing with flood disasters. This adaptation can be seen through building infrastructure, social conditions, information technology, experience, knowledge and the economy. The form of adaptation of building infrastructure is seen through the improvement of houses to two floors. The form of adaptation of knowledge and experience is carried out by minimizing the use of the first floor, and becoming more frequent to seek flood disaster information through the application of the flood early warning system. The benefits of economic adaptation, such as meeting clothing needs, are mostly obtained from assistance. The form of social adaptation can be seen from the attitude of mutual help before, during and after the flood disaster occurs. Community institutions such as cadets together with the Head of RW and Village Parties routinely hold flood disaster socialization which aims to improve the community's ability to deal with floods that occur.